UK Referendum and Potential Brexit? - John Ryan (ifo Schnelldienst, 2016)
– Vortrag von Prof. John Ryan, London School of Economics and Political Science
Keywords: E42; F15; F33; F59; 330; EU-Mitgliedschaft; Exit-Strategie; Referendum; Eurozone; Großbritannien